2019
DOI: 10.1631/fitee.1800514
|View full text |Cite
|
Sign up to set email alerts
|

Task planning in robotics: an empirical comparison of PDDL- and ASP-based systems

Abstract: Robots need task planning algorithms to sequence actions toward accomplishing goals that are impossible through individual actions. Off-the-shelf task planners can be used by intelligent robotics practitioners to solve a variety of planning problems. However, many different planners exist, each with different strengths and weaknesses, and there are no general rules for which planner would be best to apply to a given problem. In this article, we empirically compare the performance of state-of-the-art planners t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 25 publications
3
23
0
Order By: Relevance
“…However the graph of |đť‘…| with planning time (Fig. 14) follows a similar trend to that reported in [33].…”
Section: Validation and Scalabilitysupporting
confidence: 79%
See 3 more Smart Citations
“…However the graph of |đť‘…| with planning time (Fig. 14) follows a similar trend to that reported in [33].…”
Section: Validation and Scalabilitysupporting
confidence: 79%
“…Their task planner is based on Answer Set Programming (ASP) [32]. Jiang et al [33] focus exclusively on task planning in robotics, assuming that a feasible motion plan exists for the synthesized task plan. They provide a comparison between ASP-based and PDDL-based task planners using different benchmark domains and conclude that PDDL-based planners perform better on tasks with long solutions, and ASP-based planners tend to perform better on shorter tasks.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…PDDL was developed for the International Planning Competition (IPC) and has been maintained by the IPC community. A recent empirical comparison has shown that PDDL-based planners perform better when tasks require long solutions, and ASP-based planners perform better when tasks require complex reasoning (Jiang et al, 2019b). The goal of implementing both ASP-based and PDDL-based planners is to provide evidence for our hypothesis that PETLON is not sensitive to task planner selection.…”
Section: Algorithm Instantiationmentioning
confidence: 99%